Report of the presence of phlebotomus (phlebotomus) salehi mesghali in Sri Lanka: A potential cutaneous leishmaniasis vector - Gajapathy, K.; Surendran, S.N. (BioMed Central Ltd, 2012)
Cutaneous leishmaniasis (CL) is emerging as a serious public health threat in Sri Lanka and more than 2000 cases have been reported during the past nine years. The parasite responsible for CL has been identified as Leishmania donovani zymodeme MON -37. Phlebotomus (Phlebotomus) salehi is a proven vector of oriental sore or CL in India. Phlebotomus (Euphlebotomus) argentipes sensu lato, which is a vector of L. donovani that causes visceral leishmaniasis (VL) in India, is suspected to be a vector of CL in Sri Lanka. But the vector of CL in Sri lanka is yet to be determined. Cattle- baited collection and hand picking techniques were used for sandfly collection in three CL endemic localities, namely, Vavuniya, Anuradhapura and Trincomalee. Female Ph. (Phl.) salehi flies from the collections were identified based on morphological and published morphometric characters. This is the first record of the presence of Ph. (Phl.) salehi in the country.
Keywords: Leishmaniasis; Phlebotomus (Phlebotomus) salehi; Sandfly; Sri Lanka; Vector